Regenerative Therapy in Degenerative Joint Disease - Muhammad Yusuf Ginanjar; Irma Ruslina Defi; Muhammad Luthfi Dharmawan; Istingadah Desiana (Rifa'Institute, 2026)
Introduction: Degenerative joint disease is a major cause of disability and functional limitation, particularly in the elderly, and conventional treatments are often limited to symptomatic relief without addressing structural degeneration. Objective: This study aims to review the mechanisms of action and clinical effectiveness of regenerative therapies in the management of degenerative joint disease. Method: A literature review was conducted by analyzing relevant scientific articles, including clinical trials, systematic reviews, and experimental studies focusing on platelet-rich plasma, mesenchymal stem cells, prolotherapy, and regenerative hydrogels. Result and Discussion: Regenerative therapies show the ability to reduce pain, improve joint function, and support tissue repair through biological mechanisms such as anti-inflammatory effects, cell proliferation, and extracellular matrix regeneration. Platelet-rich plasma shows consistent benefits in early-stage disease, while mesenchymal stem cells offer potential for long-term structural regeneration. Prolotherapy provides a simple and cost-effective alternative, and hydrogels enhance therapeutic delivery and tissue support, especially in combination therapies. However, variability in protocols and limited long-term evidence remain key challenges. Conclusions: Regenerative therapy represents a promising approach for degenerative joint disease management, but further standardized and long-term studies are required to optimize clinical application and ensure safety and effectiveness